The Consequences of Individual Perception on Non-Financial Performance Measurement Systems - Lina, Lina (Universitas Pelita Harapan, 2023)
This study aims to develop a conceptual model that describes the consequences of individual perception of non-financial performance measurement systems based on the social exchange theory. The application of non-financial performance measurement may be associated with the perception of increased procedural fairness in the performance measurement process. Furthermore, performance measurements based on various non-financial measures tend to increase subordinates' trust in their superiors. Job satisfaction can be increased by increasing subordinates' trust in superiors. Trust between superiors and subordinates reflects openness to each other. This openness encourages open communication and can increase job satisfaction. Finally, job satisfaction that represents work attitude must be related to job performance.